Down-regulation of HLA class II and costimulatory CD86/B7-2 on circulating monocytes from melanoma patients - Ugurel, Selma; Schadendorf, Dirk (Cancer immunology immunotherapy, 2004)
Antigen-presenting cells are crucial for the induction of an antigen-specific antitumoral immune response. Deteriorations in the expression pattern of cell surface molecules important for the presentation of antigens might therefore be indicative of an impaired immune response status in cancer patients. In the present study we investigated the expression of MHC class I and class II molecules, of the costimulatory molecules CD80/B7-1 and CD86/B7-2, of the adhesion molecule CD11c, and of the marker of activation CD71 on CD14+ peripheral blood monocytes (PBMs) from 144 melanoma patients in different stages of disease and 43 healthy controls, by flow cytometric analysis. We found a decreased expression of HLA-DR (p<0.0005), HLA-DQ (p=0.006), HLA-DP (p<0.0005), and CD86/B7-2 (p=0.001) on PBMs from melanoma patients compared with healthy controls, whereas no significant difference could be detected in the expression of HLA class I antigens and CD80/B7-1. This down-regulated expression was associated with disease progression. In contrast, CD71 expression was stage-dependently increased on PBMs from melanoma patients compared with healthy controls (p=0.024). No correlation was found between the PBM surface expression pattern and age, gender, tumor load, and current mode of therapy of the patients. The observed down-regulation of HLA class II and CD86/B7-2 on melanoma patients’ PBMs might reflect an ineffective antigen-presenting function contributing to an impaired antigen-specific immune response in these patients.